Gender-specific experiences of serious mental illness in rural Ethiopia: A qualitative study. Issue 2 (1st February 2020) - Ghebrehiwet, Senait; Baul, Tithi; Restivo, Juliana L.; Kelkile, Teshome Shibre; Stevenson, Anne; Gelaye, Bizu; Fekadu, Abebaw; Hailemariam, Maji; Girma, Eshetu; Teferra, Solomon; Canelos, Victoria; Henderson, David C.; et al.
ABSTRACT: Considerable variation in the gender-specific prevalence of serious mental illness (SMI) has been reported in low- and middle-income countries (LMICs). In the rural setting of Butajira, Ethiopia, the male-to-female prevalence ratio of schizophrenia was reported to be 5:1. This qualitative study explores gender-specific experiences of SMI and the extent to which sociocultural factors may explain the observed difference in prevalence estimates. Using purposive sampling, 39 in-depth interviews were conducted with community members from Butajira, a rural district in South Central Ethiopia. Transcripts were analysed using thematic analysis to elicit community perspectives on cultural explanatory models of SMI and experiences in this region. Gender-specific experiences were reported to differ due to visibility of symptoms, community responses, and varying levels of family support towards individuals with SMI. Overall, respondents described how various sociocultural factors subject women with SMI to higher levels of physical and social isolation compared to men, greatly affecting community health workers' ability to identify and provide care to women with mental illness. Future case detection methods should involve family members as they interact with women with SMI early on in the development of their symptoms and play an essential role in their path to mental health care.